2020
DOI: 10.1155/2020/9146727
|View full text |Cite
|
Sign up to set email alerts
|

Research on Active Intelligent Perception Technology of Vessel Situation Based on Multisensor Fusion

Abstract: In this paper, we focus on the safety supervision of inland vessels. This paper especially aims at studying the vessel target detection and dynamic tracking algorithm based on computer vision and the target fusion algorithm based on multisensor. For the vessel video target detection and tracking, this paper analyzes the current widely used methods and theories. Additionally, facing the application scenarios and characteristics of inland vessels, a comprehensive vessel video target detection algorithm is propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Situational awareness refers to the ability to perceive the ship's state, navigation posture and other information when the ship is navigating autonomously, to ensure that the ship can fully perceive the complex relationship between the ship and the surrounding situation [20] . Current research on situational awareness mainly focuses on the development of an intelligent situational awareness system [21] and the improvement of perception accuracy [22] . Of the 18 articles searched on the Web of Science using the keywords AIS, ships and situational awareness, the types of research and their percentages are shown in Figure 3 below.…”
Section: The Perceptual Layermentioning
confidence: 99%
“…Situational awareness refers to the ability to perceive the ship's state, navigation posture and other information when the ship is navigating autonomously, to ensure that the ship can fully perceive the complex relationship between the ship and the surrounding situation [20] . Current research on situational awareness mainly focuses on the development of an intelligent situational awareness system [21] and the improvement of perception accuracy [22] . Of the 18 articles searched on the Web of Science using the keywords AIS, ships and situational awareness, the types of research and their percentages are shown in Figure 3 below.…”
Section: The Perceptual Layermentioning
confidence: 99%
“…Fuzzy logic Multi-factor fuzzy [58,81,104,116,124,126,185,207] For the kinematic analysis, most of the implementations are based on trajectory analysis, like trajectory clustering [171] or similarity [179]. Kalman filters, the Ornstein-Uhlenbeck target motion model, and the Gaussian mixture model are also used for kinematic behavior analysis.…”
Section: Neural Networkmentioning
confidence: 99%
“…Li et al [ 11 ] used the ship head features in the transformed domain of polar coordinates for the classification of support vector machines to improve the accuracy of ship detection. However, the performance of these algorithms depends mainly on the designed features description of the ship targets, while the overall operation efficiency is governed by the qualities of feature extraction and classifiers [ 12 , 13 , 14 ]. In addition, although the traditional machine learning algorithms are relatively strong in classification, they are weak in generalization, and lack adaptability to environmental changes and multi-scale features of the targets [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%